Infrared thermography application to rate emotional states in sports - Kozhevnikova, I. S.; Pankov, M. N.; Startseva, L. F. (Theory and Practice of Physical Culture, 2019)
Competitions and sports are thought of as extreme human activity, requiring serious mobilization of individual`s physical and mental resources. Outstanding performance in sporting activities depends largely on athlete`s psychoemotional state. In this context, there is an actual problem of the reliable and unbiased evaluation of athlete`s psychoemotional state using not only subjective assessment, but also instrumental methods. One of new perspective methods is the digital infrared thermography. Twenty-one young men and ladies at the ages from 19 to 26, who have been actively involved in sporting and competitive activities not less than three years, participated in our research. We obtained thermal images of examinees in positive and negative emotional states. For statistical analysis we used the statistics of the second order based on gray-level co-occurrence matrices. We compared average color intensity, standard deviation, average brightness, coefficients of excess and asymmetry, energy and entropy, contrast and homogeneity. The reliable differences in the region of noses of the examinees with negative and positive emotional reactions were detected in result of statistical analysis.